The Gawain-Poet and the Fourteenth-Century English Anticlerical Tradition. - Campbell, Ethan (Research in Medieval and Early Modern Culture Ser., 2018)
"Ethan Campbell argues that a central feature of the Gawain-poet's Middle English works' moral rhetoric is anticlerical critique. Written in an era when clerical corruption was a key concern for polemicists such as Richard FitzRalph and John Wyclif, as well as satirical poets such as John Gower, William Langland, and Geoffrey Chaucer, the Gawain poems feature an explicit attack on hypocritical priests in the opening lines of Cleanness as well as more subtle critiques embedded within depictions of flawed priest-like characters."--